Gradient Estimates for Spacelike Mean Curvature Flow with Boundary Conditions. Issue 2 (29th November 2018) - Lambert, Ben
Abstract: We prove a gradient estimate for graphical spacelike mean curvature flow with a general Neumann boundary condition in dimension n = 2. This then implies that the mean curvature flow exists for all time and converges to a translating solution.